Portugal : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
A range of indicators point to a competitiveness gap of 10-20 percent with respect to euro area competitors. Closing the competitiveness gap will require an extended adjustment period, even with a jump in total factor productivity (TFP) growth and strong wage moderation. This paper reviews several factors that could help explain the boom and bust behavior of corporate investment. Investor sentiment will recover with the deepening of structural reforms, but high corporate debt level is likely to slow the pace of investment growth in the near future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet